Can social isolation alleviate symptoms of anxiety and depression disorders? - Peçanha, Amanda; Silveira, Bruna; Krahe, Thomas E.; Landeira Fernandez, Jesus (Frontiers in Psychiatry, 2025)
This study examines the complex interplay between social behavior and mental health, focusing on the neurobiological mechanisms underlying human interactions and their alterations associated with anxiety and depression disorders. These conditions are characterized by heightened threat perception, pervasive worry, physiological responses, emotional dysregulation, and maladaptive behaviors. Through narrative review, this study examines both aspects, addressing social isolation as both a risk factor and an avoidance behavior that may provide temporary relief but ultimately perpetuate the clinical condition in the long term. The findings offer valuable insights for clinical practice, emphasizing interventions that enhance cognitive flexibility to foster stable and supportive interpersonal relationships.